Factors and processes of gibbsite formation in Northern Thailand - L. Herrmann (2018)
Gibbsite is usually considered as end product of weathering in tropical environments with potentially high leaching rates. However, there are also hints towards gibbsite formation in initial stages of weathering in different climates. This study reports on a systematic approach based on soil forming factors in order to research the conditions of gibbsite formation in northern Thailand highlands. Therefore, three major study sites were chosen, which differ with respect to parent rock, relief, climate and vegetation. The results show that gibbsite is common in soils of the area. Reasons for its occurrence in soils are manifold. It can be a heritage of the parent rock, a result of initial weathering under free draining conditions or an accumulation under intense chemical weathering caused by high rainfall. Especially the investigation in granite and gneiss areas with a high share of primary minerals indicates that gibbsite can be an early and direct transformation without intermediates from micas and feldspars if free drainage is assured. With progressing soil genesis clay formation reduces drainage and favours kaolinite formation. Only sites with extremely high rainfall and low evaporation (high elevations in northern Thailand) show again a dominance of gibbsite in the clay fraction throughout the whole soil profile. © 2007 Elsevier B.V. All rights reserved.